Estudo dos mecanismos de resolução inflamatória em animais tratados com angiotensina-(1-7) em modelos murinos de artrite - Lívia Corrêa Barroso (2013)
During inflammatory responses, leukocytes, produce and secrete mediators responsible for the initiation and maintenance of inflammation. Inflammation may be beneficial and protects the body against harmful agents. However, when uncontrolled, it can lead to tissue damage. Thus, there is much interest in understanding mechanisms that control and resolve the inflammatory response, as well as mediators and cells involved in this process. Recently, it was observed that Angiotensin-(1-7), a metabolite of Renin-Angiotensin system may control the inflammatory response. Therefore, the objective of this study was to evaluate whether endogenous production or exogenous administration of Ang-(1-7) could control the resolution of the inflammatory response in models of arthritis in mice. In this study, all treatments were given 12 hous after the injection of antigen in order to separate anti-inflammatory from pro-resolutive effects. The intra-articular administration of Ang-(1-7) decreased the number of neutrophils in the synovial cavity and in periarticular tissues, increased the number of apoptotic cells and inhibited translocation of Nf- B in a model of antigen-induced arthritis in mice. Treatment with DIZE, an activator of ACE2 which induces generation of Ang-(1-7), induced effects which were similar to those observed with the administration of Ang-(1-7). Resolution of inflammation was reversed by use of the inhibitor of caspases Zvad-FMK, indicating that the action of Ang-(1-7) was inducing apoptosis of neutrophils. Indeed, Ang-(1-7) was also able to directly induce apoptosis of human neutrophils in vitro. The latter effect was associated with inhibition of the activation of NF- B in neutrophils. Therefore, we conclude that Ang-(1-7) has pro-resolutive effects on inflammation and may be useful for the treatment of diseases in which the accumulation of neutrophils may have a pathophysiological role.